Simone Weil and the specter of self-perpetuating force - Doering, E. Jane (University of Notre Dame Press, 2010)
""Simone Weil and the Specter of Self-Perpetuating Force is a definitive contribution not only to Weil studies, but to any effort to understand the problem of violence and the sources of peace. The study seamlessly blends narratives of Weil's life and thought during the early twentieth century with those of people, political movements, and events pivoting on the world stage. E. Jane Doering helps to frame a plausible case for the optimism Weil forged in the fire of her own suffering: there is a counterforce to violence, and it is available when we attend to life beyond the delusions we habitually cultivate."--Ann Pirruccello, University of San Diego" ""E. Jane Doering's book provides us a new, more penetrating focus on the central message of Simone Weil. The m̀ine of pure gold' that Weil referred to in her last days is sharply delineated here: the possibility of grace as the countervailing power that may efficaciously oppose oppressive force. Doering's research is impeccable and opens new perspectives for Weil scholars for years to come."--John Marson Dunaway, Mercer University" "Simone Weil's philosophical and social thought during her short life (1909-1943) was intimately engaged with the nature of power and force, both human and natural, and the problems inherent in the use of force. Weil argued vehemently for pacifism, then moved in the context of the rise of Nazism toward a guarded acceptance of the use of force under very specific circumstances. E. Jane Doering carefully examines and analyzes the material in Weil's notebooks and lesser-known essays to illuminate her evolving thought on violence, war, and injustice. In addition, Doering addresses Weil's engagement with the Bhagavad-Gita during her final years, a text that reoriented and enlightened Weil's activist and intellectual search for moral value in a violent world. The book contains Doering's expert translations of numerous notebook entries."--Jacket